ANALISIS KEBIJAKAN DESENTRALISASI SISTEM PENDIDIKAN NASIONAL DAN DAMPAKNYA TERHADAP LEMBAGA PENDIDIKAN DI INDONESIA - Nursahwal; Yuspiani (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
This article aims to analyze decentralization policies in Indonesia’s national education system and to identify their impact on the implementation of education. The method employed in this study is library research. Data were collected by reviewing and examining various relevant sources, particularly journal articles related to the topic. The data analysis was conducted descriptively. The findings indicate that the decentralization policy, established through Law No. 22 of 1999 and later refined by Law No. 32 of 2004, marked a shift in education management from a centralized to a decentralized model, with the expectation of improving effectiveness, efficiency, and relevance to local needs. The policy has brought positive outcomes, such as increased regional participation, greater management efficiency, school autonomy, and stronger community involvement in decision-making. However, several challenges remain, including disparities in education quality between regions, limited infrastructure, weak managerial capacity, and unequal budget distribution. Decentralization in the national education system cannot be regarded as an instant solution for educational equity; rather, it must be accompanied by efforts to strengthen local government capacity, establish effective collaboration with the central government, and ensure proper oversight mechanisms. This article highlights the necessity of a collaborative strategy among the central government, local authorities, and educational institutions to achieve sustainable equity in access and improvements in education quality.